Influence of Agroforestry Buffers on Soil Hydraulic Properties Relative to Row Crop Management. Issue 8 (August 2016) - Akdemir, Eda; Anderson, Stephen H.; Udawatta, Ranjith P.
Abstract : Abstract: Agroforestry and grass buffers have been developed as part of the management system for row crop areas in temperate regions to improve soil and water quality and diversify farm income. A study was conducted to evaluate the influence of agroforestry and grass buffers relative to row crop management on soil hydraulic properties (saturated hydraulic conductivity, soil water retention, and pore size distribution) for a claypan soil. The experimental watersheds for this project were located at the Greenley Memorial Research Center. The paired watersheds for the study area were under no-till management with a corn ( Zea mays L.)–soybean ( Glycine max L.) rotation since 1991. The agroforestry buffer watershed and grass buffer watershed had vegetative buffer strips planted between row crop areas, which were 4.5 m wide and 36.5 m apart with vegetation composed of grasses, legumes, and trees. Throughout the grass buffer and agroforestry buffer strips, redtop ( Agrostis gigantea Roth), brome grass ( Bromus spp.), and birdsfoot trefoil ( Lotus corniculatus L.) were planted. For the agroforestry buffers, pin oak ( Quercus palustris Muenchh), swamp white oak ( Quercus bicolar Willd.), and bur oak ( Quercus macrocarpa Michx.) trees were planted. Soil cores were taken from four 10-cm depth increments with 6 replicates, and hydraulic and physical properties were determined. Significant differences ( P < 0.05) were found among the treatments for bulk density, with the row crop treatment having higher values compared with the buffer treatments. Trends also showed higher saturated hydraulic conductivity for the agroforestry buffer treatment compared with the row crop treatment for the 0 to 10 cm and 30 to 40 cm soil depths. These buffer treatments slightly improved soil hydraulic properties after 17 years for this claypan soil.